Agency, Intelligence and Reasons in Animals. (2nd September 2019) - Glock, Hans-Johann
Abstract: What kind of activity are non-human animals capable of? A venerable tradition insists that lack of language confines them to 'mere behaviour'. This article engages with this 'lingualism' by developing a positive, bottom-up case for the possibility of animal agency. Higher animals cannot just act, they can act intelligently, rationally, intentionally and for reasons. In developing this case I draw on the interplay of behaviour, cognition and conation, the unduly neglected notion of intelligence and its connection to rationality, the need to recognize that reasons are objective conditions, and the difference between the ability to act for reasons and the capacity to reflect on reasons.